Volatility Patterns in Indian Stock Market before and After Introduction of Securities Lending and Borrowing Scheme - P, Swarna Lakshmi (Ushus Journal of Business Management, 2014)
The securities lending and borrowing scheme was introduced in India on 21st April 2008. This paper tries to evaluate whether the scheme have impact on Indian stock market. The volatility of the NSE CNX NIFTY is measured before and after the introduction of the scheme using ARCH (1) model. If the scheme had attracted more participants then more borrowing and lending might have taken place which might have increased volatility. Our results revealed that the volatility has not increased but instead decreased. Hence, the scheme might not have got active participation and the reasons for that are discussed. Alternatives such as selling futures instead of borrowing, the costs associated with the scheme, the difficulty in retailer participations and all seem to be the flaws. SEBI has made many changes in the scheme after introduction, like changing the tenure and allowing preclosure of the contract etc. But, unless the problems related to cost and stock available for trading are solved, other changes cannot attract people towards this scheme.